Spiders (Aranei) of the Lower Volga Region (Astrakhan and Volgograd areas of Russia) with the description of new taxa - A.V. Ponomarev; E.A. Belosludtsev; .V. Dvadnenko (Кавказский энтомологический бюллетень, 2008)
Based on the original material and literature data the annotated species list of spiders is presented for the Lower Volga Region (the Astrakhan and Volgograd areas of Russia). At present 254 species from 23 families are recorded in the region. Of them in the Astrakhan area — 177 species from 22 families, in Volgograd area — 149 species from 19 families are revealed. The genus Bogdocosa Ponomarev et Belosludtsev gen. n. (Lycosidae) with type species Bogdocosa baskuntchakensis Ponomarev et Belosludtsev sp. n. is described from the Astrakhan area of Russia. The new species Haplodrassus caspius Ponomarev et Belosludtsev sp. n. (Gnaphosidae) from the Astrakhan area of Russia and Atyrau areas of Kazakhstan is descrabe